TECHNIQUE IN TEACHING LITERATURE - Jaftiyatur Rohaniyah (OKARA: Jurnal Bahasa dan Sastra, 2012)
This article tries to explore a particular technique in literature classroom. Literature is a content subject and compulsory subject, such as: poetry, prose, drama, etc. which give for the college students who take course in English language education. The paper focuses on using small group discussion technique included pre-discussion activities, whilst-discussion activities, and postdiscussion activities and how to implement them in teaching English poetry for the EFL/ESL students of English language education program. This technique is intended to help students in improving their poetry comprehension and motivating them to learn literary subject especially poetry.